2015
DOI: 10.1186/s13054-015-0749-4
|View full text |Cite
|
Sign up to set email alerts
|

Transferring the critically ill patient: are we there yet?

Abstract: During the past few decades the numbers of ICUs and beds has increased significantly, but so too has the demand for intensive care. Currently large, and increasing, numbers of critically ill patients require transfer between critical care units. Inter-unit transfer poses significant risks to critically ill patients, particularly those requiring multiple organ support. While the safety and quality of inter-unit and hospital transfers appear to have improved over the years, the effectiveness of specific measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
1
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 77 publications
2
112
1
17
Order By: Relevance
“…Rural trauma and urgent care systems coordinate the initial emergency medical services (EMS) response, organize rapid transfers to smaller health centers, and quickly refer to trauma or tertiary centers when appropriate. 2 Specialized retrieval teams within these systems have evolved over the past few decades, 9 with the goal to improve care and expedite both scene and interfacility transports to the trauma or tertiary center. Evidence from recent military conflicts suggested that specialized trauma retrieval teams are effective and achieve improved survival outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Rural trauma and urgent care systems coordinate the initial emergency medical services (EMS) response, organize rapid transfers to smaller health centers, and quickly refer to trauma or tertiary centers when appropriate. 2 Specialized retrieval teams within these systems have evolved over the past few decades, 9 with the goal to improve care and expedite both scene and interfacility transports to the trauma or tertiary center. Evidence from recent military conflicts suggested that specialized trauma retrieval teams are effective and achieve improved survival outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Kulshrestha and Singh (2016) reinforce this idea while also emphasizing that the decision to transport a patient based on the benefit-risk assessment and its planning based on team communication and risk score are essential to determine the risk of transport, both for the patient and the transport team. Droogh, Smit, Absalom, Ligtenberg, and Zijlstra (2015) argue that, despite the use of scores, the transport itself can also influence the severity score to the extent that inter-hospital transport is associated with the risk of physiological deterioration and adverse events. This risk is proportional to the patient's level of severity before the transport and the team's level of experience and knowledge.…”
Section: Transport Risk Scorementioning
confidence: 99%
“…The internal medicine unit was responsible for 69% of transfers, followed by the general surgery unit (28.8%), which can be associated with the population ageing in the region (200 elderly people per 100 young people in 2015; Base de Dados Portugal Contemporâneo, 2015) and, consequently, with an increased number of associated medical conditions (Direção-Geral da Saúde, 2014). In a literature review, Droogh et al (2015) concluded that the number of transfers is likely to increase with the centralization of specialized care. Wiegersma et al (2011) found that specialist consultations or advanced/specialized therapy were the main indications for transfer, which is in line with the results found in this study, where 38% of patients were transferred to be examined by specialist and 37% to perform specialized therapeutic interventions.…”
Section: Characterization Of the Clinical Profilementioning
confidence: 99%
“…This serves to ensure that any complications which may arise during the IPT can be identified and addressed immediately, thus optimizing the overall patient safety equation during transport. Figure 3 demonstrates major possible risks associated with IPTs, and Figure 4 summarizes the IPT risk assessment process, highlighting the multitude of interdependent factors that may contribute (alone or in various combinations) to the occurrence of adverse events during interfacility patient transport [4,76,77].…”
Section: Advanced Life Support (Als) Versus Basic Life Support (Bls):mentioning
confidence: 99%